2017
DOI: 10.5152/iao.2017.2723
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Association between Sudden Hearing Loss and DNA N-Methyltransferase 1 (DNMT1) Genetic Polymorphism

Abstract: This study's results showed that the AA genotype in rs2228611 polymorphism was a risk factor in ISSHL patients and the GG genotype could be a protective factor in rs2228612 polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Metal overload and epigenetic changes may also affect the cochlea or the sensorial epithelium, playing a role in various forms of sensorineural hearing loss. [77,78]. These facts were observed by the same group, describing how iron homeostasis genes predispose to one of the most difficult and complex forms of hearing loss, i.e., idiopathic sudden sensorineural hearing loss [79].…”
Section: Molecular Genetics and Epigeneticsmentioning
confidence: 76%
“…Metal overload and epigenetic changes may also affect the cochlea or the sensorial epithelium, playing a role in various forms of sensorineural hearing loss. [77,78]. These facts were observed by the same group, describing how iron homeostasis genes predispose to one of the most difficult and complex forms of hearing loss, i.e., idiopathic sudden sensorineural hearing loss [79].…”
Section: Molecular Genetics and Epigeneticsmentioning
confidence: 76%
“…Increased risk was determined by a significantly higher SNP frequency observed in affected SSNHL subjects compared to controls. In contrast, the following seven genes had at least one SNP correlated with a decreased risk: APOE , DNMT1 , FCRL3 , GRHL2 , GPX3, HSPA1A , SERPINE1 (23–29) (Supplemental Digital Content, Table 1, http://links.lww.com/MAO/B337). Decreased risk was inferred by the observation of a significantly lower SNP frequency in SSNHL subjects compared to controls, or by a significantly higher SNP frequency in controls compared to SSNHL subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased risk was inferred by the observation of a significantly lower SNP frequency in SSNHL subjects compared to controls, or by a significantly higher SNP frequency in controls compared to SSNHL subjects. Interestingly, there were two genes, DNMT1 and FCRL3, for which specific genotypes in different SNPs of each gene were found to have opposite associations with SSNHL risk (23,25).…”
Section: Gene Target Association With Ssnhl Susceptibilitymentioning
confidence: 99%
“…Twenty-two genetic studies were included. 5,7,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] These genetic studies sought to find genetic variants associated with the development of SSNHL and their results are summarized in Table IV.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…6 Only 10%-15% of cases have known causes, and the rest are considered idiopathic. 1,7 The heritability of SSNHL is largely unknown, and few studies have compared SSNHL prevalence among populations with different ethnic backgrounds or explored familial aggregation. Some genetic studies have identified allelic variants potentially linked to an increased risk of SSNHL, particularly in prothrombotic factors.…”
Section: Introductionmentioning
confidence: 99%